Government of Meghalaya Tenth Five Year Plan 2002-2007 and Annual Plan 2002-2003 Draft Proposals Volume - II - Planning Commission (Planning Commission, 2002)
Employment market information in District Employment Exchange, Williamnagar 4. Strengthening o f Divisional Employment Exchange, Shillong 5. Vocational Guidance Unit in District Employment Exchange, Williamnagar 6. Incentive to SC/ST in Coacing-cum- Guidance Centre, Shillong 7. Sub-Divisional Employment Exchange, Nongpoh/ Mairang/ Ampati/Baghmara 8. Employment Information & Assistance Bureau, Amlarem/ Pynursla/Dadengiri 9. Construction of buildings for Employment Exchanges. CRAFTSMEN TR A IN ING 1. Setting up of I.T.Is at Nongstoin /Nongpoh/Williamnagar/Baghmara 2. Advance course in the trade o f Dress Making 3. Introduction o f new trades in I.T.I. Shillong/Tura/Jowai/For women/Nongstoin 4. Incentive Scheme to I.T.I. Trainees 5. Acquisition of land/construction of buildings for I.T.Is. 6. Strengthening o f Vocational Training Wing in Directorat
General Statement and Annexures